Utilization of Ultraviolet C Light-Emitting Diodes for the Deactivation of SARS-CoV-2 in Human Breath - Sobotka, Piotr; Przychodzki, Maciej; Staniszewska, Monika; Rutkowska, Katarzyna (Photonics Letters of Poland, 2024)
Ultraviolet light has a long track record when it comes to use for deactivating harmful microorganisms. With recent developments in LED technology in terms of generating electromagnetic waves from this specific spectral range, new applications have emerged. In this study, the possibility of constructing an effective miniature UV barrier for deactivating the SARS-CoV-2 virus in both exhaled and inhaled air is investigated. Our findings demonstrate that utilizing commonly available UVC diodes operating at the wavelength of 275 nm makes it possible to attain an adequate level of deactivation that fulfills the standards specified for commercial devices. Full Text: PDF References N.G. Reed, "The History of Ultraviolet Germicidal Irradiation for Air Disinfection", Public Health Rep. 125(1), 15 (2010) CrossRef S. Oliveira De Souza, A. Cardoso, A. Sales, C. Sarmento, F. D’errico, "Effectiveness of a UVC air disinfection system for the HVAC of an ICU", Eur. Phys. J. Plus 137, 37 (2022), CrossRef N. Trivellin et al., "UV-Based Technologies for SARS-CoV2 Inactivation: Status and Perspectives", Electronics 10, 4 (2021), CrossRef R. S. Bergman, "Germicidal UV Sources and Systems", Photochem. Photobiol. 97(3), 466 (2021), CrossRef M. Shatalov, R. Jain, T. Saxena, A. Dobrinsky, M. Shur, "Chapter Two - Development of Deep UV LEDs and Current Problems in Material and Device Technology", Semiconductors and Semimetals 96, 45 (2017). CrossRef W. Kowalski, Ultraviolet Germicidal Irradiation Handbook UVGI for Air and Surface Disinfection, 1 (2009), CrossRef P. Sobotka, M. Przychodzki, K. Uściło, T.R. Woliński, M. Staniszewska, "Effect of Ultraviolet Light C (UV-C) Radiation Generated by Semiconductor Light Sources on Human Beta-Coronaviruses’ Inactivation", Materials 15(6), 2302 (2022), CrossRef Y. Gerchman, H. Mamane, N. Friedman, M. Mandelboim, "UV-LED disinfection of Coronavirus: Wavelength effect", J. Photochem. Photobiol. B Biol. 212, 112044 (2020), CrossRef R.M. Mariita, J.W. Peterson, "Not all wavelengths are created equal: disinfection of SARS-CoV-2 using UVC radiation is wavelength-dependent", Access Microbiology 3(11), 1 (2021), CrossRef Polio laboratory manual, 4th ed., World Health Organization 2004. DirectLink J.V. Maizel, D.O. White, M.D. Scharff, "The polypeptides of adenovirus: I. Evidence for multiple protein components in the virion and a comparison of types 2, 7A, and 12", Virology 36(1), 115 (1968), CrossRef H. Inagaki, A. Saito, H. Sugiyama, T. Okabayashi, S. Fujimoto, "Rapid inactivation of SARS-CoV-2 with deep-UV LED irradiation", Emerging Microbes and Infections 9(1), 1744 (2020), CrossRef